PEMBERDAYAAN POTENSI LOKAL BERBASIS DIVERSIFIKASI PERTANIAN DAN DIGITALISASI UMKM DI DESA GRENDEN KECAMATAN PUGER - Asna, Asna; Arifudin, Moch. (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
Food security is a strategic issue that requires comprehensive and integrated management, particularly in rural areas that possess abundant natural resources but continue to face limitations in the development of food diversification. This study aims to analyze efforts to optimize local potential through agricultural diversification and the digitalization of Micro, Small, and Medium Enterprises (MSMEs) as part of the implementation of the Community Service Program (Kuliah Kerja Nyata/KKN) in Grenden Village, Puger District, Jember Regency. A participatory approach was employed by involving the community as active partners at every stage of the program, including socialization activities, training in agricultural product processing, the adoption of business digitalization, and assistance with business legality. The program primarily focused on the development of value-added corn-based processed products, such as corn nuggets and corn syrup, which represent the village’s leading commodities. The results of the program indicate an improvement in community capacity to process agricultural products in a hygienic, innovative, and value-oriented manner, as well as to utilize digital platforms for product marketing. Furthermore, assistance with business legality provided access to legal protection and expanded opportunities for sustainable business development. The findings demonstrate that community-based food diversification strategies supported by MSME digitalization significantly contribute to strengthening food security, improving community welfare, and creating new economic opportunities at the village level. This study offers practical contributions to the development of food security and MSME empowerment through the synergy between the KKN program and the sustainable utilization of local potential.